ANALISIS DAN PENGEMBANGAN BUKU AJAR KIMIA KELAS X SEMESTER I SMK FARMASI SESUAI KTS - Boni Mariska Ratnawati; Ramlan Silaban; Eddiyanto Eddiyanto (Jurnal Pendidikan Kimia (JPKim), 2014)
Abstract. This research aims to (1) Analyze the chemistry handbooks used in the vocational school of Pharmacy in North Sumatra, (2) Develop a sequence of chemical material suitable to grade X semester I and systematically according to KTSP of Pharmacy Vocational School, (3) Knowing what chemical materials worth and the right to be taught in Pharmacy vocational school grade X semester I so that learning is more systematic and easily understood by BSNP students in learning, (4) Developing the chemistry handbook for grade X semester I Pharmacy Vocational School appropriate with KTSP, and (5) Knowing the opinion of teachers of chemistry at Pharmacy Vocational School on the development of standard chemistry handbook of grade X semester I. Sample in this study are two publishers of chemistry handbooks used in grade X  semester I of the most widely used in Pharmacy Vocational School in North Sumatera, has graduated from the book center, and marketed nationally and four vocational school chemistry teacher used grade X Pharmaceuticals as a respondent and has teaching experience in grade X Pharmacy Vocational School for a minimum of two years and a minimum education is bachelor degree (S1). This is a research development using qualitative data described by using the time sentence by emphasizing the documentary technique. This research instrument is a questionnaire with a book containing sheets of the feasibility of the indicators derived from the assessment of National Education Standards Agency (BSNP) in 2006, later identified occurrence for each book. Furthermore it is developing chemistry handbook for grade X semester I Pharmaceuticals appropriate vocational curriculum, which will be assessed by the respondent chemistry teachers of Pharmacy Vocational School. The assessment results of validation between the average range to determine whether or not worthy of the book used in grade X semester I of Pharmacy Vocational School. The results of the feasibility analysis of the contents of the handbooks most widely used chemical in the first semester of the grade X is obtained percentage Pharmacy Vocational School: books A, and B are, respectively 51.89% and 76.01%. Validation range obtained in the proposed grade X semester I of chemical materials Pharmacy Vocational School is 3.6 means that the proposal put forward appropriate materials are used in the development of chemistry handbooks for grade X semester I Pharmacy Vocational School. Assessment chemistry handbook for grade X semester I Pharmacy Vocational School on the feasibility of content, language, and presentation by chemistry teacher of Pharmacy Vocational School respondents obtained an average yield of the range of validation in order are 3,31; 3,52, and 3,51. Validation of the overall range obtained from the four respondents chemistry teacher of Pharmacy Vocational School is 3.45, this means that the Chemistry Handbook for Grade X Semester I Pharmacy Vocational School According With KTSP is valid and does not need to be revised again and have been feasible to use in chemistry learning in Pharmacy Vocational School.Keywords: Chemistry Handbook, Pharmacy Vocational School, Analysis, Development, KTSP